Seasonal and spatial comparisons of microzooplankton grazing and phytoplankton growth in the Bohai Bay, China - Wen, Yujian; Zhang, Guodong; Song, Yuyao; Zhang, Guicheng; Sun, Jun (Frontiers in Marine Science, 2023)
The dilution experiment technique was used in two cruises in July-August (summer) and October-November (autumn) 2020, with a total of 14 stations. The grazing impact of microzooplankton on phytoplankton in the interior of Bohai Bay was comprehensively investigated. We compared phytoplankton growth rates (μ0) and microzooplankton grazing rates (m) spatially (distance between experimental stations and shore far vs. near) and seasonally (summer vs. autumn). Both m and μ0 values were significantly higher in summer than in autumn, and the phytoplankton growth rate μ0 was positively correlated to temperature. Offshore stations showed higher values. There is no significant spatial and seasonal differences in the ratio of microzooplankton grazing rate and phytoplankton growth rate (m/μ0) indicating that daily consumption of primary production by microzooplankton was similar in the two seasons. Therefore, our research showed a close coupling between microzooplankton grazing with phytoplankton growth in the Bohai Bay.